Effectiveness of a state-of-the-art coat with fans and coolants over standard coats - Sofia Villaveces; Zhaochong Yu; Mohana Priya; Lorenna Altman; Qichen Fang; Ryan Bellacov; Rosalyn Davis; Kermit Davis; Ashley Kubley; Myoung Ok Kim; Mark Schulz; Vesselin Shanov; et al. (International Journal of Thermofluids, 2025)
Objective: Firefighters use personal protective equipment when containing fires. The coat, called standard hereafter, that is part of the personal protective equipment has not changed for many years. A new coat was designed with novel features. Its inner layer is made of a carbon nanotube-based fabric, two pouches with coolants, and fans. The new coat and standard coat were to be compared on several metrics including core body temperature, heart rate, heart rate variability, heat storage, aerobic capacity, Borg scale, Thermal Comfort scale, and Respiratory Distress in a live burn facility. Principle results: The new coat was significantly better than the standard coat on all metrics with one exception, namely, Thermal Comfort scale. The coats significantly impact the average core body temperature across all epochs with p < 0.0001. They also impact heart rate with p < 0.0001, heart rate variability with p = 0.0019, and heat storage with p < 0.0001. Major conclusion: One important mission for any coat was to ensure that the core body temperature does not reach the hyperthermia level temperature (38° C) when a firefighter is working inside a live burn facility. The new coat worked on this count better than the standard coat with p = 0.0144.